PSO BASED MULTI-OBJECTIVE OPTIMIZATION FOR DISTRIBUTION PLANNING WITH DISTRIBUTED GENERATION - Sugiarto, Sugiarto (Institut Teknologi Nasional Yogyakarta, 2018)
This paper presents a multi-objective function for optimal placement of distributed generation (DG) resources in distribution systems in order to minimize the power losses and improve voltage profile. Particle swarm optimization (PSO) and weight method are applied to the proposed technique to obtain the best compromise between these costs. Simulation results on IEEE 30-bus test system are presented to demonstrate the usefulness of the proposed procedure.